The Mediating Role of Emotional Intelligence in the Relationship Between School Principals’ Sustainable Leadership Behaviors and Diversity Management Skills - Çayak, Semih; Eskici, Menekşe (Frontiers in Psychology, 2021)
The purpose of this research is to examine the mediating role of emotional intelligence in the relationship between school principals' sustainable leadership behaviors and their diversity management skills. For this purpose, this research, which was designed in the relational survey model, was carried out on a total of 402 teachers, 224 of which were females (56%) and 178 were males (44%). The data of the study were collected using the “Sustainable Leadership Scale”, “Diversity Management Scale” and “Emotional Intelligence Scale”. Descriptive statistics, Pearson product-moment correlation coefficient, t-test, one-way Anova analyzes and structural equation model were used in the analysis of the data. As a result of the research, it was found that the school principals' sustainable leadership behavior levels, their ability to manage differences and their emotional intelligence levels were high according to teacher perceptions. According to the correlation analysis, it was found that there is a positive and significant relationship between sustainable leadership, diversity management and emotional intelligence. In addition, path analyzes to examine the mediator variable effect revealed that emotional intelligence has a full mediating role in the relationship between school principals' sustainable leadership behaviors and their diversity management skills. In addition to the research, it was also examined whether teachers perceptions of school principals on sustainable leadership behaviors, diversity management skills and emotional intelligence levels differ significantly according to teachers' gender, professional seniority, educational status and the level of education they work in. In addition to this, they have shown that they need to use their emotional intelligence effectively.